2014
DOI: 10.1158/2326-6066.cir-13-0198
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Depolymerizing Agents Used in Antibody–Drug Conjugates Induce Antitumor Immunity by Stimulation of Dendritic Cells

Abstract: Antibody-drug conjugates (ADC) are emerging as powerful treatment strategies with outstanding targetspecificity and high therapeutic activity in patients with cancer. Brentuximab vedotin represents a first-in-class ADC directed against CD30 þ malignancies. We hypothesized that its sustained clinical responses could be related to the stimulation of an anticancer immune response. In this study, we demonstrate that the dolastatin family of microtubule inhibitors, from which the cytotoxic component of brentuximab … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 47 publications
2
101
0
4
Order By: Relevance
“…The recent findings of Zippelius et al [9294] suggest that ADCs, especially those made with the potent microtubule-disrupting agents as the payload, may be combined with immune checkpoint inhibitors such as anti-PD1 antibodies (pembrolizumab, nivolumab) or anti-PD-L1 antibodies (atezolizumab) for enhanced and sustained anti-tumor effect. Not only do such ADCs induce immunogenic cell death, but the ADC-mediated tumor accumulation of a potent microtubule agent appears to activate intra-tumor dendritic cells, inducing uptake of antigens and the migration of antigen-loaded dendritic cells to lymph nodes where they can trigger activation of T-cells which may be directed towards tumor-associated antigens [9295].…”
Section: The Place Of Adcs In the Treatment Of Solid Tumorsmentioning
confidence: 99%
“…The recent findings of Zippelius et al [9294] suggest that ADCs, especially those made with the potent microtubule-disrupting agents as the payload, may be combined with immune checkpoint inhibitors such as anti-PD1 antibodies (pembrolizumab, nivolumab) or anti-PD-L1 antibodies (atezolizumab) for enhanced and sustained anti-tumor effect. Not only do such ADCs induce immunogenic cell death, but the ADC-mediated tumor accumulation of a potent microtubule agent appears to activate intra-tumor dendritic cells, inducing uptake of antigens and the migration of antigen-loaded dendritic cells to lymph nodes where they can trigger activation of T-cells which may be directed towards tumor-associated antigens [9295].…”
Section: The Place Of Adcs In the Treatment Of Solid Tumorsmentioning
confidence: 99%
“…The induction of tumour cell death following ADC therapy may allow the expression of tumour antigens that, in conjunction with the immune checkpoint blockade, facilitate a host T cell response against the tumour. A recent preclinical study has shown that brentuximab vedotin is a potent inducer of dendritic cell (DC) maturation [86]. This study identified that, in addition to the cytotoxic capabilities of this ADC, brentuximab vedotin can stimulate a host adaptive immune response in both patient and animal models.…”
Section: Recent Antibody–drug Conjugate Developmentsmentioning
confidence: 99%
“…It was first described in 2003 and acts by binding to CD30 with high affinity, consequently releasing MMAE into the cytosol where it induces cell cycle arrest and apoptosis [25]. Beyond this mechanism of action, there is evolving evidence that MMAE may promote antitumor immunity by activating tumorresident dendritic cells (DCs) [26]. Over a period of 10 years, it has become evident that DCs, besides being potent antigen-presenting cells, occur in the tumor microenvironment as regulatory DCs, contributing to immune evasion by tumors.…”
Section: Brentuximab Vedotinmentioning
confidence: 99%